Water quality Part 2. Physical, chemical and biochemical methods Sec 2.19 Methods for determination of cyanogen chloride (BSI, 1986)
Water, Quality, Water testing, Water resources, Potable water, Wastes, Sewage, Trade effluents, Effluents (sewage), Determination of content, Chlorides, Cyanides (inorganic), Nitriles, Chemical analysis and testing, Colorimetry, Spectrophotometry, Interferences (chemical), Testing conditions, Test equipment, Dimensions, Calibration, Safety measures, Concentration (chemical)